Arrhythmias in children - Matsuno, Alessandra Kimie (Medicina (Ribeirao Preto), 2012)
This paper presents a review of mechanisms, epidemiology, diagnosis and treatment of major arrhythmiasin children. If unrecognized and untreated, arrhythmias in children may lead to life-threatening hemodynamic instability. Therefore, early recognition and immediate treatment of these patients in the emergency department are essential.